(untitled) (International Journal of Applied Research in Management and Economics, 2023)
Globally, unhealthy diets have a significant impact on people’s risk of disease and mortality, so the German Ministry of Nutrition and Agriculture also focuses on healthier and balanced diets in its reduction and innovation strategy. By means of the Nutri-Score, the nudging principle is used to provide consumers with additional nutritional labelling and to encourage the purchase of healthier foods. The aim of this study is to investigate the effectiveness of visual nudging in FMCGs, i.e., the food industry, in the form of the Nutri-Score on consumers’ purchase decisions and to validate its robustness with respect to demographic factors. For this purpose, an online survey was conducted with 294 participants leading to a total number of up to 3,528 observations regarding their purchase intention of selected products. A logistic regression analysis showed that the purchasing behaviour changed with the insertion of the Nutri-Score per se and with subjects avoiding negatively rated products and preferring positively rated ones. It was further shown that these effects persist regardless of participants’ demographics.